The TaGSK1, TaSRG, TaPTF1, and TaP5CS Gene Transcripts Confirm Salinity Tolerance by Increasing Proline Production in Wheat (Triticum aestivum L.) - Murat Aycan; Marouane Baslam; Toshiaki Mitsui; Mustafa Yildiz (Plants, 2022)
Salinity is an abiotic stress factor that reduces yield and threatens food security in the world’s arid and semi-arid regions. The development of salt-tolerant genotypes is critical for mitigating yield losses, and this journey begins with the identification of sensitive and tolerant plants. Numerous physiologic and molecular markers for detecting salt-tolerant wheat genotypes have been developed. One of them is proline, which has been used for a long time but has received little information about proline-related genes in wheat genotypes. In this study, proline content and the expression levels of proline-related genes (TaPTF1, TaDHN, TaSRG, TaSC, TaPIMP1, TaMIP, TaHKT1;4, TaGSK, TaP5CS, and TaMYB) were examined in sensitive, moderate, and tolerant genotypes under salt stress (0, 50, 150, and 250 mM NaCl) for 0, 12, and 24 h. Our results show that salt stress increased the proline content in all genotypes, but it was found higher in salt-tolerant genotypes than in moderate and sensitive genotypes. The salinity stress increased gene expression levels in salt-tolerant and moderate genotypes. While salt-stress exposure for 12 and 24 h had a substantial effect on gene expression in wheat, TaPTF1, TaPIMP1, TaMIP, TaHKT1;4, and TaMYB genes were considerably upregulated in 24 h. The salt-tolerant genotypes showed a higher positive interaction than a negative interaction. The TaPTF1, TaP5CS, TaGSK1, and TaSRG genes were found to be more selective than the other analyzed genes under salt-stress conditions. Despite each gene’s specific function, increasing proline biosynthesis functioned as a common mechanism for separating salt tolerance from sensitivity.